General English-Kurdish Dictionaries in Terms of Meeting the User's Needs (Raparin Journal of Humanities (RJH), 2024)
User perspective is an approach in which lexicography is studied from the users' perspectives. The study of dictionary users improve the quality of dictionaries. This paper aims at studying general English-Kurdish dictionaries, available in print, offline and online formats, in terms of meeting the needs of users and their level of satisfaction.This study has adopted the survey methodology and an online questionnaire is adminsterd as a quantitative method of data collection. Different users of bilingual dictionaries were asked to participate in this survey, and to achieve this goal, a number of users filled in the forms. The data was analysed through SPSS 2022 program. The research population consists of speakers of Central Kurdish in the three provinces of Erbil, Sulemani and Halabja. They are classified according to the variables of gender and level of education. The main objectives of this study are to identify the users' cross-reference needs, and other needs due to which users refer to dictionaries, as well as the relation between these needs and the variables of sex and education level. The main findings are as in the following: the users' choice of dictionary format is not different based on the variables of gender and level of education. The primary reason for users to employ dictionaries is for receptive purposes (reading and understanding), with productive purposes (speaking and writing) being a secondary consideration.